Nitrogen availability mediates the priming effect of soil organic matter by preferentially altering the straw carbon-assimilating microbial community - Bei, Shuikuan; Li, Xia; Kuyper, Thomas W.; Chadwick, David R.; Zhang, Junling (The Science of the total environment, 2022)
Straw incorporation into soil increases carbon (C) sequestration but can induce priming effects (PE), the enhanced breakdown of soil organic matter. The direction and magnitude of PE and the consequences for the C balance induced by straw addition depend on nitrogen (N) availability and soil management history. Using 13C-labeled maize straw, we conducted a 56-day incubation to determine the dynamics of PE and the underlying microbial mechanisms after straw and/or mineral N addition to three soils with contrasting cultivation and fertilization histories, i) unfertilized soil (Unfertilized), ii) 8 years farmyard manure amended soil (Manured), and iii) abandoned cropland soil (Abandoned). 13C-PLFAs (phospholipid fatty acids) were analyzed to identify microbial groups utilizing straw and to explore their contribution to the PE. Straw addition increased microbial biomass (MBC), activities of enzymes related to the C and N cycles, and changed microbial community composition. SOC decomposition was enhanced by microbes activated by straw addition, leading to a positive cumulative PE ranging from 494 to 789 μg C g−1 soil. The magnitude of positive PE and straw decomposition in the manured soil was higher than that in the unfertilized and abandoned soils due to larger MBC and higher enzyme activities, resulting in a lower net SOC gain. Compared with straw only, the combination of straw addition with N fertilizer did not influence MBC, but increased positive PE (average increase of 18.1%) and straw decomposition (17.1%), further limiting SOC gain. 13C-labeled fungi: bacteria ratios and Gram-positive (G+): negative (G−) bacteria ratios increased with the increasing PE after N fertilization, but soil-derived (un-labeled) PLFAs remained stable. Random forest analysis further showed that straw C-assimilating microbial attributes are important predictors in driving the greater PE after N addition. Our study highlights the importance of straw C-assimilating fungi and G+ bacteria in mediating N-induced PE in arable soils. [Display omitted] •Nitrogen inputs induced higher soil enzyme activities and positive PE intensity.•Nitrogen inputs had no effect on MBC but led to higher 13C-labeled fungi: bacteria and G+:G− ratios.•13C-PLFA of bacteria decreased and actinomycetes increased with prolonged incubation time.•Straw carbon assimilating microbial communities were important predictors of greater PE intensity induced by N addition.